Art Therapy as Means of Development of Emotional Intelligence of Preschool Children - Y. V. Lazareva; A. E. Rudakova (Научный диалог, 2018)
The article is devoted to the development of emotional intelligence of preschool children using art therapy. The relevance of the study is determined by the need to develop the potential of the child in the field of interaction with other people, to form the resource of social success. The article contains a review of scientific publications aimed at the study of human emotional intelligence, as well as the study of a set of art therapeutic methods effective in working with children. The definitions of such phenomena as “art therapy,” “emotional intelligence” are given. The author offers the definition of the concept “emotional intelligence.” Attention is paid to the structure of emotional intelligence. The content of its components, such as the perception of emotions, identification of emotions, understanding of the causes of their occurrence is considered. An important part of the article is the results of a diagnostic examination of emotional intelligence of children of preschool age. The results of a comparative analysis of the level of development of emotional intelligence of children before the formative experiment and after its completion are presented. It is proved that the use of such art methods as the reflection of the emotional states of a person through drawing, role-playing emotional states, joining the emotional states of the characters through literary work contribute to the development of such components of emotional intelligence as perception, identification of emotions, determining the causes of their occurrence.